1998
DOI: 10.1001/archinte.158.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Autologous Donation Decreases Allogeneic Transfusion but Increases Exposure to All Red Blood Cell Transfusion<subtitle>Results of a Meta-analysis</subtitle>

Abstract: Preoperative autologous donation of blood decreases exposure to allogeneic blood but increases exposure to any transfusion (allogeneic and/or autologous). There is a direct relationship between the transfusion rate in the control group and the benefit derived from preoperative autologous donation. This suggests that other methods of decreasing blood transfusion, such as surgical technique and transfusion protocols, may be as important as preoperative autologous donation of blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(129 citation statements)
references
References 41 publications
5
112
0
9
Order By: Relevance
“…However, it should not be interpreted that preoperative autologous blood donation reduced all sources of blood transfusion or perioperative blood loss. Results of two meta-analyses regarding the effect of preoperative autologous blood donation on the need for blood transfusion showed that preoperative autologous blood donation not only reduces exposure to allogenic blood but also may increase exposure to all red blood cell transfusion in some types of surgical procedures, such as total joint arthroplasty 22,23 . This happens because preoperative autologous blood donation decreases the preoperative hemoglobin level, which is the most important predictor of perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should not be interpreted that preoperative autologous blood donation reduced all sources of blood transfusion or perioperative blood loss. Results of two meta-analyses regarding the effect of preoperative autologous blood donation on the need for blood transfusion showed that preoperative autologous blood donation not only reduces exposure to allogenic blood but also may increase exposure to all red blood cell transfusion in some types of surgical procedures, such as total joint arthroplasty 22,23 . This happens because preoperative autologous blood donation decreases the preoperative hemoglobin level, which is the most important predictor of perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of autologous blood transfusion for elective orthopaedic surgery is decreasing, despite an overall upward trend in transfusion rates driven by an increase in allogeneic transfusions [7,45]. The decrease in this practice may be attributable to growing concerns regarding its cost-effectiveness and utility in patients without anemia [4,6,18,20], the possibility of iatrogenic anemia leading to increased overall transfusion rates [9,12,19], and some reports suggesting no differences regarding postoperative mortality and infection compared with allogeneic transfusions [9,30]. It therefore is possible that patients of higher socioeconomic status are asking for preoperative donation of blood to their own detriment, and, paradoxically, disadvantaged populations may not be receiving substandard care.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 Yet, unfortunately, because autologous blood is considered safe, it is transfused more liberally and total exposure to any blood product is increased. 2 This attitude towards autologous blood is inappropriate because errors do occur in a considerable proportion of cases. A recent Canadian study documented an error rate of 1/149 autologous units collected.…”
Section: Discussionmentioning
confidence: 99%
“…1 Results of a recent meta-analysis reveal that predeposition of autologous blood decreases allogeneic transfusion considerably and that the benefit of autologous blood donation (ABD) is greatest when the expected use of blood is highest. 2 In cardiac surgery, autologous blood programs are similarly successful. The probability of receiving allogeneic blood decreased from 82% to 27%, and from 69% to 32% in the studies by Owings et al and Dzik et al respectively.…”
Section: Occasional Reviewmentioning
confidence: 99%